Polymerization of hemoglobins in Arctic fish: Lycodes reticulatus and Gadus morhua. - Riccio A; Giordano D; Flagiello A; Tedesco R; Bruno S; di Prisco G; Verde C.; MANGIAPIA, GAETANO; VERGARA, ALESSANDRO; MAZZARELLA, LELIO; PUCCI, PIETRO; PADUANO, LUIGI (IUBMB Life, 2011)
In vitro, and possibly in vivo, hemoglobin polymerization and red blood cell sickling appear to be widespread in codfish. In this article, we show that the hemoglobins of the two Arctic fish Lycodes reticulatus and Gadus morhua also have the tendency to polymerize, as monitored by dynamic light scattering experiments. The elucidation of the primary structure of the single hemoglobin of the zoarcid L. reticulatus shows the presence of a large number of cysteyl residues in α and β chains. Their role in eliciting the ability to produce polymers was also addressed by MALDI-TOF and TOF-TOF mass spectrometry. The G.morhua globins are also rich in Cys, but unlike in L. reticulatus, polymerization does not seem to be disulfide driven. The widespread occurrence of the polymerization phenomenon displayed by hemoglobins of Arctic fish supports the hypothesis that this feature may bea response to stressful environmental conditions.